2011
DOI: 10.1182/blood-2010-07-294678
|View full text |Cite
|
Sign up to set email alerts
|

Postrelapse survival in childhood acute lymphoblastic leukemia is independent of initial treatment intensity: a report from the Children's Oncology Group

Abstract: While intensification of therapy has improved event-free survival (EFS) and survival in newly diagnosed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 42 publications
5
55
0
Order By: Relevance
“…25,39 Finally, our data on ETV6/RUNX1-positive ALL from the FRALLE 93 study can probably be extended to other first-line protocols because Freyer et al recently showed that postrelapse survival in relapsed childhood ALL was independent of initial treatment intensity. 38 In conclusion, the prognosis of patients with relapses of ETV6/RUNX1-positive ALL occurring more than 36 months after diagnosis is excellent. Testicular relapses are particularly common which suggests that a primary treatment able to cross the testicular barrier should be used and that follow-up should be prolonged with careful screening of the gonads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,39 Finally, our data on ETV6/RUNX1-positive ALL from the FRALLE 93 study can probably be extended to other first-line protocols because Freyer et al recently showed that postrelapse survival in relapsed childhood ALL was independent of initial treatment intensity. 38 In conclusion, the prognosis of patients with relapses of ETV6/RUNX1-positive ALL occurring more than 36 months after diagnosis is excellent. Testicular relapses are particularly common which suggests that a primary treatment able to cross the testicular barrier should be used and that follow-up should be prolonged with careful screening of the gonads.…”
Section: Discussionmentioning
confidence: 99%
“…However, the poor survival rate of patients with early relapses encourages the use of a second-line treatment with cell therapy according to the REZ-BFM. In both types of relapse, 38 clinical decisions could also be helped by assessing the dynamics of treatment response using minimal residual disease quantification, which is a promising strategy being validated in ongoing relapse trials. 25,39 Finally, our data on ETV6/RUNX1-positive ALL from the FRALLE 93 study can probably be extended to other first-line protocols because Freyer et al recently showed that postrelapse survival in relapsed childhood ALL was independent of initial treatment intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years significantly increased the effectiveness of ALL treatment in the pediatric group of patients (Freyer et al, 2011). Surveillance, Epidemiology and End Results register (SEER) analysis showed the biggest improvement in survival of patients aged 15-19 years because the 5-year overall survival increased from 41 to 62%.…”
Section: Treatment Of Acute Lymphoblastic Leukemia Patientsmentioning
confidence: 99%
“…13 Contributing to the inferior OS of older patients is the observation that those ÏŸ15 years of age treated for relapsed ALL have a significantly worse outcome than their younger peers. 14 Infants, those Ïœ1 year of age at the time of diagnosis, remain at very high risk of relapse, even with aggressive contemporary therapy. 15,16 Risk stratification within the infant group is based on presence of MLL gene rearrangement, found in Ïł75% and in the majority of younger infants.…”
Section: Clinical Featuresmentioning
confidence: 99%